Chemical method for the gallium arsenide rectification structure divide into crystals [Articol] - Baranov, Simion; Cinic, Boris; Dudca, Tudor; Suman, Victor (UTM, 2009)
This investigations are referred to power semiconductor devices (PSD) area manufactured by gallium arsenide (GaAs) advanced technology. The work’s objective is excluding the break-down effect on the p-n junction surface of high voltage devices, which is advance progressed with diminishing the crystal dimensions in the dividing process of the semiconductor structures. We propose the method of the GaAs deep etching by a mixture utilizing concentrated acids as nitric and hydrochloric acids in equal rates. After 30 min of mixing up the solution formation is consorted of the endothermic reaction, bound up by nitrosyl chloride (NOCl) formation, which dissolves the GaAs decomposed product in solution by arsenic oxidation up to As(V), forming ortoarsenic acid and gallium chloride. This method is used for dividing semiconductor structure of GaAs with 0.4-0.6 mm of thickness in small dimensioned crystals. The advantages of this technology are the great speed of GaAs dissolving, low costs of manufacturing and profitableness.
Keywords: gallium arsenide; dissolution; chemical divide of the structure in crystals